Development and Validation of a Fast Ultra-High Performance Liquid Chromatography–Fluorescent Method for the Quantification of Hydroxychloroquine and Its Metabolites in Patients With Lupus. Issue 4 (August 2019) - Noé, Gaëlle; Amoura, Zahir; Combarel, David; Lori, Lesli; Tissot, Nadine; Seycha, Aguila; Funck-Brentano, Christian; Zahr, Noël
Abstract : Background: Hydroxychloroquine (HCQ) is approved for the treatment of systemic lupus erythematosus (SLE). Therapeutic drug monitoring of HCQ is necessary to detect nonadherence and to improve treatment efficacy in patients with SLE. Liquid chromatographic–tandem mass spectroscopy and high performance liquid chromatography (HPLC)–fluorescent methods are currently used to measure whole blood concentrations of HCQ and its 2 main metabolites desethylhydroxychloroquine and desethylchloroquine in patients with SLE. This study reports the development and validation of an ultra-HPLC (U-HPLC) method with fluorescence detection for the simultaneous quantification of HCQ and its metabolites in whole blood. Methods: After adding chloroquine (internal standard) to the samples, a single-step protein precipitation and a subsequent filtration were used for blood sample preparation. Analytes were separated under isocratic elution on a U-HPLC RP18 column with a total run time of 7 minutes. The mobile phase consisted of piperazine buffer (46.4 mM, pH = 9.8) and acetonitrile (68:32, vol/vol), which was delivered at a flow rate of 0.4 mL/min. Fluorescence excitation and emission wavelengths were 335 and 390 nm, respectively. Assay performance parameters were evaluated per FDA bioanalytical guidelines. Results: The calibration curve was linear from 125 to 4000 ng/mL for HCQ. The lower limit of quantification was 10 ng/mL for all analytes. For HCQ, desethylchloroquine, and desethylhydroxychloroquine, accuracies and imprecisions ranged from −7.90% to 7.85% and 1.14% to 8.78%, respectively. Conclusions: A sensitive, accurate, and fast U-HPLC–fluorescent method was validated and successfully applied to quantify whole blood concentrations to perform therapeutic drug monitoring of HCQ in pediatric and adult lupus patients.